Poverty in the Palu Koro Fault Hazard Area, Central Sulawesi and its Influencing Factors. - Adfar, Mohamad (Maneggio, 2024)
Disaster areas are important to study, especially the level of poverty and the factors that influence it, especially the Gross Regional Domestic Product factor, Income Inequality of people including the Population and the Length people took the study in the school within a period of 10 years, namely from 2014-2023. Poverty has always been a benchmark for the success of development in a region which is always associated with and has implications for low levels of education, health, physical security and reduces the quality of life of community. Government efforts continue to be made to reduce poverty levels, Of course studies from various institutions are needed as input for policy makers in the Region. The use of quantitative research methods was chosen by the author to analyze the problems in this study using multiple regression with time series data from three regions, namely Donggala Regency, Palu City and Sigi Regency. The data used in this study are secondary data from 2014-2023 obtained from the official publication of the Central Statistics Agency (BPS). The results of the study show that the Gross Regional Domestic Product (GRDP) in the Palu Koro fault disaster area does not have a significant effect on Poverty, while Income Inequality has a negative and significant effect on Poverty, as well as the Population has a negative and significant effect on Poverty while the variable of  the Length people took the study in the school the area has a significant and positive effect on the increase in the Number of Poverty from 2018 to 2023.